Nitrogen addition and mowing affect microbial nitrogen transformations in a C4 grassland in northern China - Wang, C.; Butterbach-Bahl, K.; He, N.; Wang, Q.; Xing, X.; Han, X. (European Journal of Soil Science, 2015)
Microbial nitrogen (N) transformations play a key role in regulating N cycling in grassland ecosystems. However, there is still little information on how management of semi-arid grassland such as mowing and/or N fertilizer application affects microbial activity and N transformations. In a field experiment in northern China, N was added at a rate of 10 g N m(-2) year(-1) as NH4NO3 to mown and unmown plots (4 x 4 m(2)) and in situ rates of net ammonification (R-amm), nitrification (R-nit) and mineralization (R-min) were followed at monthly intervals for the vegetation growth periods in the years 2006-2009. In addition, we also measured soil microbial biomass carbon (MBC) and nitrogen (MBN), microbial respiration (MR) and peak above-ground biomass in August of each measurement year. Driven by the pronounced inter-annual variability of rainfall, all the properties investigated varied markedly across years. Nevertheless, we were able to demonstrate that over the 4 years N addition significantly stimulated R-nit, R-min and MBN, on average, by 288, 149 and 11.6%, respectively. However, N addition decreased MBC significantly as well as the ratio of MBC:MBN by, on average, 10 and 23%, respectively, whereas an effect of N addition on MR could not be demonstrated. Mowing decreased MBN, MR and qCO(2) significantly by 9, 28 and 24%, respectively, but no effects were found on microbial net N transformation rates and MBC. N addition and mowing interactively affected R-amm and R-min, and MBN, MBC:MBN. In summary, our results indicate a positive effect of N addition but a negative effect of mowing on microbial N transformation in this C4 grassland in northern China.